2017
DOI: 10.19173/irrodl.v18i5.2892
|View full text |Cite
|
Sign up to set email alerts
|

Nonnative English-Speaking Students’ Lived Learning Experiences With MOOCs in a Regular College Classroom

Abstract: The goal of this study was to gain in-depth understanding about nonnative English-speaking students' lived experiences with massive open online courses (MOOCs) in a regular college classroom. Phenomenological methodology was used to examine those experiences in 24 Korean college students. Individual interviews, an open-ended online survey, observation notes, online weekly journal entries, and social media constituted the data sources. Findings show that students' lived experiences included (a) wonder and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Considering that 75% of learners in this study were located outside the United States, its infrequency is somewhat surprising. However, other studies show that nonnative English-speaking students forgo posting in Web-based forums when they lack confidence in their English writing skills [32], when their cultures do not place a high value on dialogue [33], and when their learning preferences do not include group discussions [32]. Therefore, it could be that nonnative speakers opted not to post questions, thereby reducing the instances of this emergent code.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that 75% of learners in this study were located outside the United States, its infrequency is somewhat surprising. However, other studies show that nonnative English-speaking students forgo posting in Web-based forums when they lack confidence in their English writing skills [32], when their cultures do not place a high value on dialogue [33], and when their learning preferences do not include group discussions [32]. Therefore, it could be that nonnative speakers opted not to post questions, thereby reducing the instances of this emergent code.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be that nonnative speakers opted not to post questions, thereby reducing the instances of this emergent code. Likewise, some international students, including Koreans, may learn English with a focus on correct grammar rather than on speaking and listening skills; these students may decide not to post to forums [32]. In this study, there were 3.58% (54/1509) of spelling and grammar errors that could be interpreted as an annoyance to other learners; these instances may prove to be a minor price for the much larger added benefit of encountering diverse perspectives from a variety of countries.…”
Section: Discussionmentioning
confidence: 99%
“…One important indicator suggesting that a learner is likely to succeed in a course, is their engagement in discussion forums through conversations, because it requires some level of English language fluency. Cho and Byun [6] reported that there is very little evidence on how English as a second Language (ESL) participants study in MOOCs. As Kizilcec et al [7] explain, people from Least Developed Countries where English is typically not the primary language, may feel discouraged because of their fear of being seen as less capable through their poor language skills.…”
Section: Introductionmentioning
confidence: 99%
“…English as a second Language Learners' (ESL) engagement on a MOOC which is delivered in English ( [6,[31][32][33][34]).…”
mentioning
confidence: 99%
See 1 more Smart Citation